Analisis Kapasitas Kebijakan dalam Penataan dan Pemberdayaan Pedagang Kaki Lima di Kawasan Alun-Alun Kota Bandung dengan Pendekatan Policy Capacity - Fairuz Zahra Fuadi; Didin Muhafidin; Sawitri Budi Utami (CV. Creative Tugu Pena, 2025)
This study examines the arrangement and empowerment of street vendors (PKL) in the Alun-Alun Kota Bandung area, which continue to face various challenges despite policy reforms introduced through Regional Regulation Number 11 of 2024. The research aims to analyze the policy capacity of the Bandung City Government using the policy capacity framework, encompassing analytical, operational, and political dimensions at the individual, organizational, and system levels. A descriptive qualitative method was employed through observation, in-depth interviews with 10 informants, and documentation studies. The findings reveal that analytical capacity has not been fully based on the actual needs of street vendors, as reflected in the low occupancy rate of relocation sites. In the operational dimension, policy implementation remains ineffective due to limited coordination and resources. Meanwhile, in the political dimension, the policy has not gained strong legitimacy because of the minimal participation of street vendors in the policymaking process. These findings indicate that the limitations of policy capacity are systemic in nature, highlighting the need for comprehensive strengthening to achieve more effective and sustainable policies